Bilingual Education at the post-secondary level; A Case Study - Edwards, Viviane (Canadian Journal of Higher Education, 1989)
In 1983, the University of New Brunswick adopted a French Language Policy which called for courses to be offered in French in a number of disciplines, including Economics, History and Political Science. This article discusses the events which led to the adoption of the Policy and the difficulties as well as successes which the Policy has met since its adoption. In spite of being supported unanimously by the Deans and in spite of having a fairly large population of eligible candidates at the university, courses continue to suffer from low enrollment. The article provides information on enrollment since 1984 as well as the university policy for the support of French language study by members of faculty.